Reproducibility and interobserver variability of systolic blood flow velocity and 3D wall shear stress derived from 4D flow MRI in the healthy aorta. Issue 1 (3rd July 2015) - van Ooij, Pim; Powell, Alexander L.; Potters, Wouter V.; Carr, James C.; Markl, Michael; Barker, and Alex J.
Abstract : Purpose: To investigate the reproducibility and interobserver variability of 3D aortic velocity vector fields and wall shear stress (WSS) averaged over five systolic timeframes derived from noncontrast 4D flow magnetic resonance imaging (MRI). Materials and Methods: Fourteen controls underwent test‐retest 4D flow MRI examinations separated by 16 ± 3 days (resolution = 3.0–3.6 × 2.3–2.6 × 2.5–2.7 mm 3 ; TE/TR/FA = 2.5/4.9 msec/7°; Venc = 150 cm/s). Two observers segmented the aorta, and WSS was calculated for both series of scans and both segmentations. Test–retest and interobserver velocity and WSS vectors were compared on a voxel‐by‐voxel basis in the aorta and on a regional basis by subdividing the aortas in six segments. Results: Test–retest: voxel‐by‐voxel Bland–Altman analysis revealed small differences (–0.03/–0.02 m/s/Pa), limits of agreement (LOA) of 0.25 m/s/0.29 Pa, and coefficients of variation (CV) of 20% for velocity/WSS. Voxel‐by‐voxel orthogonal regression analysis showed moderate agreement (slope: 1.14/1.16, intraclass correlation coefficient [ICC]: 0.76/0.67 for velocity/WSS). The regional analysis revealed a CV of 9%/8% and ICC of 0.9/0.9 for velocity/WSS. Interobserver: voxel‐by‐voxel difference for WSS was 0, LOA: 0.17/0.19 Pa, CV: 12/13%, slope: 1.01/1.09, ICC: 0.87/0.85 for test/retest. The CV/ICC for WSS in the regional analysis was 4%/1.0 for test and 3%/1.0 for retest. Conclusion: Systolic velocity and WSS derived from 4D flow MRI are reproducible between consecutive visits, with low interobserver variability in healthy volunteers. J. MAGN. RESON. IMAGING 2016;43:236–248.